Dampak Pencemaran Mikroplastik di Wilayah Pesisir Laut - Fadel Ikrar Jamika; Indang Dewata; Siti Maharani Nasution; Budhi Primasari; Yommi Dewilda (Jurnal Sumberdaya Akuatik Indopasifik, 2023)
Problems of environment life in the world are very diverse, including related pollution in coastal areas. Management coast and sea Each has its own complexity of problems, opportunities and challenges. One of the problems in coastal marine management is the problem of plastic waste pollution especially microplastics. The purpose of this research is to describe the image and impact of microplastics in coastal areas. The method used Is qualitative or review literature. Microplastic has experienced plastic degradation and a size diameter < 5mm. Source microplastic consists of namely primary and secondary. Microplastics enter coastal areas in several ways, such as flowing water from rivers, wind, and are carried by currents and some enter the sea through runoff. Pollution microplastic have broad impacts, among others health people, economy, tourism and aesthetics beach. Microplastics in the environment coast and sea cause serios damage to life sea, fish, death animal sea through winding and swallowing plastic debris.